Dinâmica educacional de Vitória da Conquista e seus efeitos locais - Mota, Crisley Tatiana Dias (2011)
The dynamic spatial location plays an important role in the production structure and together with the binding of education services is a form of competitive entry place, earning positive elements, important in the face of public policies applied at different scales. To take the first steps in this direction is to consider the service of education and, specifically, formal education offered by higher education as an element capable of transforming the space, being the starting point for this research. This form of organization more competitive and geographically concentrated institutions bringing benefits to local attractions for the allocation of other economic sectors such as trade, services and construction, showing that education in addition to being essential for the formation of citizen is also capable of contributing to local economic development and other sites connected in a network system. Given the above, this study aims to analyze the dynamics of the education sector as production of the geographical area of Vitoria da Conquista, on the assumption that Vitoria da Conquista constitutes a Local Productive Arrangement based on the consolidation of an educational center , and therefore promote a hegemony of the city of Vitoria da Conquista in relation to other counties in the southwestern region of Bahia. Thus, this literature theoretically based work and field research has brought aspects of empirical reality to be confronted with theories. The collection of data from institutions of higher education was organized after an intentional sampling for total establishments. Also interviewed staff members who are part of the process of urban growth as representatives of the city and related agencies to local businesses. To make the work possible, it was also necessary field survey on the proposed variables in the study through open interviews and questionnaires, survey of databases of IBGE, the Regional Museum of UESB, the Municipal Government of Victoria da Conquista, municipal planning agencies, and the Master Plan of the city, seeking to understand the process by which expertise is passing the city of Vitoria da Conquista e institutions of higher education with documentary information and testimonies of those involved. To finish it is interesting to note that before the elements that make up the sector of Higher Education of Vitoria da Conquista, one can say that the process of forming a Local Productive Arrangement is being organized by higher education, which here is designated Productive Arrangement Local Educational - APL.Edu/VC Vitoria da Conquista.